Pemberdayaan Masyarakat Desa Cibitung Wetan Menuju Pertanian dan Peternakan Berkelanjutan Berbasis Bioenergi Limbah Organik - Yessie Widya Sari; Akhiruddin Maddu; Rina Mardiana; Angga Saputra; Abdurrahman Bahtiar; Dani Indrawati Berlianingtyas; Zahra Firda Santoso; Desi Alifia Putri; Ibrahim Purawiardi; Prima Zuldian; Mohamad Ikbal Hidayah; Raihan Muhammad Akmal (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The agribusiness sector and livestock are among the key contributors to waste production, which is often dumped indiscriminately, resulting in environmental pollution. Organic wastes, such as livestock manure, are also considered to have a great potential for producing energy, including biogas, which is considered a renewable source of energy. Cibitung Wetan Village, Pamijahan District, is a village that has a high potential for agricultural and livestock development, which is very suitable for biogas production and utilization. A community engagement program was conducted by a team of members from the Department of Physics and the Department of Communication and Community Development Sciences, IPB University, to target the community of Cibitung Wetan Village, Pamijahan District, particularly sheep farmers. The main goal of this program is to promote agricultural and livestock development sustainably to increase production, reducing greenhouse gases emitted to the atmosphere. The implementation of this community engagement program was conducted through four stages, including socialization, education and training on digester construction, application of digester technology, and mentoring and evaluation. In this program, a team of members from IPB University worked together with Taruna Tani Transfarmers Farmer Group, Cibitung Wetan Village, on the construction of the digester. The training activities also revealed an increase of 49% in the knowledge and attitude of the participants, as evaluated through pre-test and post-test methods. Intensive mentoring also improved the partners’ skills in the technical areas of installation, monitoring, and maintenance of the digester system. This program shows that the use of livestock and agricultural wastes through the application of the digester system can be an alternative route to self-sufficiency in energy production, can create more added value to the wastes, and can contribute to the development of community-based sustainable agriculture and livestock production systems.